‘Foodscapes’ in Bengaluru—Changing Patterns of Family Eating Out and Waste Generation - G. K. Karanth (Revue Internationale de Politique de Développement)
The objective of this paper is to reflect upon the changing culture of eating out among middle-class households in Bengaluru. While exploring the increasing differentiation of foodscapes in the city, this study examines the notion of food waste and other waste that is generated in the course of food preparation and consumption in public places. It relates the novel patterns of food consumption outside the home with the emerging patterns of family organisation and changing food tastes. With more and more Bengalureans eating out as a way of life, as entertainment and as a means of escaping the pressures of running a kitchen in a dual/multiple-income family, food waste shifts from the home to restaurants. Using observations and interviews with consumers as well as with restaurateurs, the paper reflects on the implications of these processes in terms of waste generation and waste management.